1987
DOI: 10.1007/bf00252955
|View full text |Cite
|
Sign up to set email alerts
|

A model for ultrafilterable plasma platinum disposition in patients treated with cisplatin

Abstract: A model incorporating recent information regarding the specificity of a high-performance liquid chromatographic assay for "active" platinum in plasma ultrafiltrate, and the concept of mobile and fixed metabolites, was developed for cancer patients treated with cisplatin. Model parameters were determined using plasma and urinary platinum data obtained in 20 patients. It was assumed in the model that parent drug accounted for essentially all the platinum measured in plasma ultrafiltrate in the 2 h period immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…dose of cisplatin resulted in plasma total cisplatin AUC of 3228 mg*min/ml (10,758 mmol*min/ml), and another showed that an 18-mg/m 2 (6-mg/kg) dose produced an AUC of 134 mg*min/ml free cisplatin (Kubota et al, 1993;Lopez-Flores et al, 2005). A clinically relevant level of free cisplatin in plasma of mice is considered to be 81-519 mg*min/ml (Reece et al, 1987;van Hennik et al, 1987). Taking into account that the half-life is twice as long in mice compared with humans, and the LD 10 in nude mice was found to be 3.5 mg/kg weekly, we chose the dose of 3 mg/kg every 14 days (Reece et al, 1987;Taetle et al, 1987;van Hennik et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…dose of cisplatin resulted in plasma total cisplatin AUC of 3228 mg*min/ml (10,758 mmol*min/ml), and another showed that an 18-mg/m 2 (6-mg/kg) dose produced an AUC of 134 mg*min/ml free cisplatin (Kubota et al, 1993;Lopez-Flores et al, 2005). A clinically relevant level of free cisplatin in plasma of mice is considered to be 81-519 mg*min/ml (Reece et al, 1987;van Hennik et al, 1987). Taking into account that the half-life is twice as long in mice compared with humans, and the LD 10 in nude mice was found to be 3.5 mg/kg weekly, we chose the dose of 3 mg/kg every 14 days (Reece et al, 1987;Taetle et al, 1987;van Hennik et al, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…A clinically relevant level of free cisplatin in plasma of mice is considered to be 81-519 mg*min/ml (Reece et al, 1987;van Hennik et al, 1987). Taking into account that the half-life is twice as long in mice compared with humans, and the LD 10 in nude mice was found to be 3.5 mg/kg weekly, we chose the dose of 3 mg/kg every 14 days (Reece et al, 1987;Taetle et al, 1987;van Hennik et al, 1987).…”
Section: Methodsmentioning
confidence: 99%